Task sharing: Development of evidence‐based co‐management strategy model for screening, detection, and management of diabetic retinopathy. (27th July 2018) - Shah, Mufarriq; Noor, Ayesha; Ormsby, Gail M.; Islam, Fakir Amirul; Harper, Colin Alex; Keeffe, Jill Elizabeth
Summary: Background: The number of adults with diabetes is increasing worldwide and also the number of people with diabetic retinopathy (DR), a major complication of diabetes. Task sharing in eye care for people with diabetes could address the shortage in the number of ophthalmologists and increase access to eye care services. This study investigated the opinion of eye care professionals for a checklist of tasks, which are involved in DR management, to be possibly shared by optometrists and mid‐level eye and health care workers with ophthalmologists. Methods: The study used a purposive sampling technique. All available eye and health care workers from five selected hospitals in two provinces in Pakistan were recruited. A cross‐sectional survey was conducted to investigate the potential roles of various cadres in eye care delivery for people with diabetes. Results: Ninety‐six (79%) participants including doctors ( n = 56), optometrists ( n = 29), and mid‐level eye care workers ( n = 11) responded to the survey. Two‐thirds of the participants suggested mid‐level eye care workers, while 88.5% stated that lady health workers could provide education and health promotion to people with diabetes. Most of the participants (88.5%) suggested that optometrists could share the task of dilated ophthalmoscopy with ophthalmologists for detection of DR and make referrals to ophthalmologists if needed. Ophthalmologists remained the recommended cadre to undertake the eye examinations of patients with proliferative DR and diabetic macular edema. Conclusion: This research provided an insight on how task sharing in DR management can be implemented by optimizing the roles of eye care workers.